2020
DOI: 10.1002/jobm.202000076
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and structural response of Bacillus sp. SFC 500‐1E after Cr(VI) and phenol treatment

Abstract: Bacillus sp. SFC 500‐1E, a bacterial strain isolated from tannery sediments, is able to remove Cr(VI) and simultaneously tolerate high concentrations of phenol. In this study, we used high‐resolution microscopies, fluorescence polarization techniques, and several biochemical approaches to improve our understanding about the adaptive mechanisms of this strain to survive in the presence of Cr(VI) and phenol, both individually and simultaneously. Among adaptive strategies developed by Bacillus sp. SFC 500‐1E, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
3
1
Order By: Relevance
“…Taken together with previous studies, we can suggest that the increased spo0A levels found in this work could be related to the increase in the EPS content and in the bio lm formation previously described for B. toyonensis SFC 500-1E cells exposed to Cr(VI) + phenol (Fernandez et al 2020). Moreover, Cr(VI) and Cr(III) biosorption, either surface sorption and accumulation within cells, have been other adaptive responses previously reported for this strain (Ontañon et al, 2018b).…”
Section: Final Considerationssupporting
confidence: 90%
See 3 more Smart Citations
“…Taken together with previous studies, we can suggest that the increased spo0A levels found in this work could be related to the increase in the EPS content and in the bio lm formation previously described for B. toyonensis SFC 500-1E cells exposed to Cr(VI) + phenol (Fernandez et al 2020). Moreover, Cr(VI) and Cr(III) biosorption, either surface sorption and accumulation within cells, have been other adaptive responses previously reported for this strain (Ontañon et al, 2018b).…”
Section: Final Considerationssupporting
confidence: 90%
“…Clp, a protease that functions in preventing cytoplasmic proteins aggregation and maintaining their quality (Santos et Taken together, the presented data provide clear evidence that the presence of phenol [Cr(VI) + phenol treatment] would trigger a more complete global stress response to deal with DNA and protein damage. We have previously demonstrate that B. toyonensis SFC 500-1E is unable to metabolize phenol (Fernandez et al, 2020;Ontañon et al, 2015), and the present proteomic study did not reveal enzymes involved in the aerobic degradation pathways of this compound. Thus, it could result toxic for the cell and would explain the special effort made by the strain to cope the damage.…”
Section: Cr(vi) and Global Responsecontrasting
confidence: 65%
See 2 more Smart Citations
“…Bacteria tend to form biofilms under different pressures that include the presence of toxic substances such as antibiotics and heavy metals, as well as oxygen limitation [ 40 ]. Bacillaceae strains had been reported to resist stress from heavy metals by forming biofilms [ 41 ]. The biofilm formation is a defense mechanism for bacteria, which can increase the survival rate of these bacteria under stress [ 42 ].…”
Section: Resultsmentioning
confidence: 99%